2005
DOI: 10.1111/j.1475-6773.2005.0i366.x
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is Postacute Care Use Affected by Its Availability?

Abstract: Objective. To assess the relative impact of clinical factors versus nonclinical factors--such as postacute care (PAC) supply--in determining whether patients receive care from skilled nursing facilities (SNFs) or inpatient rehabilitation facilities (IRFs) after discharge from acute care. Data Sources and Study Setting. Medicare acute hospital, IRF, and SNF claims provided data on PAC choices; predictors of site of PAC chosen were generated from Medicare claims, provider of services, enrollment file, and Area R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 16 publications
7
111
0
1
Order By: Relevance
“…22,23 Overall, 17% of veterans who underwent a lower-extremity amputation were admitted into an SRU, and of those veterans who were assessed by rehabilitation professionals after their surgeries, 23% were ultimately transferred to an inpatient rehabilitation program. In 2 separate studies, investigators looking at admission to rehabilitation programs after amputation found that rates varied geographically.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Overall, 17% of veterans who underwent a lower-extremity amputation were admitted into an SRU, and of those veterans who were assessed by rehabilitation professionals after their surgeries, 23% were ultimately transferred to an inpatient rehabilitation program. In 2 separate studies, investigators looking at admission to rehabilitation programs after amputation found that rates varied geographically.…”
Section: Discussionmentioning
confidence: 99%
“…(230) Other options are specialized rehabilitation facilities doing hip-fracture rehabilitation or rehabilitation in a skilled nursing facility depending on availability of organization and competences. (243) Most patients in Norway are treated either in a post acute specialized rehabilitation center or receive general rehabilitation in an institution similar to a skilled nursing facility.…”
Section: Rehabilitation After a Hip Fracturementioning
confidence: 99%
“…A summary of findings from studies of PAC use in Medicare indicated that using any PAC services is related to increasing age, that use is more limited for those who are married [2,[17][18][19][20][21], and that comorbid conditions that require intensive monitoring (e.g., dementia/Alzheimer disease) also increase PAC use.…”
Section: Outcomes and Explanatory Variablesmentioning
confidence: 99%
“…Changes in Medicare payment incentives to increase efficiency have reduced postacute care (PAC) use [1][2]. However, there are competing concerns that reduced utilization and changing care sites may induce adverse events [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation